(untitled) (Bangladesh Heart Journal, 2022)
Background: Acute myocardial infarction (AMI) is one of the leading cause death and disability all over the world. But, there is a lack of data about the gender influence on in-hospital outcomes of primary percutaneous coronary intervention (pPCI) among Bangladeshi patients. This study was aimed to evaluate the clinical and angiographic differences and to compare their in hospital outcomes of pPCI between male and female patients. Objective: To evaluate the gender influence on in-hospital outcome of primary PCI. Methods: This was a prospective observational study of 90 patients with ST elevation myocardial infarction ( STEMI ) treated with pPCI in the Department of Cardiology, NICVD, Dhaka, Bangladesh from April 2019 to March 2020, followed from admission until hospital discharge or death. The patients were divided equally into two groups, group ‘! (female) and group a! (male). Result : A significant difference was observed for age (61.8±10.9vs.56.5±10.7 years; p=0.02), hypertension (66.7% vs. 42.2%; p=0.02), diabetes (68.9% vs. 44.4%; p=0.01), smoking (0.0% vs. 68.9%; p<0.001), obesity (BMI- 28.3±3.8 vs. 26.5±3.9; p=0.02), troponin I (14.89±20.48 vs. 8.25±7.92; p=0.04) and pain-to-door time (281.90±88.70 vs. 240.33±80.81 minutes; p=0.04). Female had angiographically greater frequency of multivessel disease and similar distribution of infarct related artery in relation to male. The success of the procedure was similar (91.1% vs. 97.8%; p=0.18). Overall, female experienced greater incidence of in-hospital adverse events in comparison to male (28.8% vs. 13.3%; p=0.03) and significantly higher rates of severe bleeding (11.1% vs.2.2%; p=0.03) and vascular access site complications (15.6% vs. 4.4%; p=0.04). Major adverse cardiac events (MACE) were higher among females in comparison to males (11.1% vs. 6.7%; p=0.45). Females experienced significantly higher rates of short-term net adverse clinical events (NACE) than males (20.0% vs. 8.8%; p=0.04). Female sex [odds ratio (OR) 1.94], age e”60 years (OR 1.59) and diabetes (OR 2.75) were identified as independent predictors of adverse in-hospital outcomes among STEMI patients undergoing pPCI. Conclusion: Female sex presented with significantly more risk factors and experienced more in-hospital adverse outcomes than male in STEMI patients undergoing pPCI. They had significantly higher rates of NACE, largely driven by increased rate of major bleeding. Female sex was an independent predictor for the development of in-hospital adverse outcomes in STEMI patients undergoing pPCI. Bangladesh Heart Journal 2022; 37(1): 40-51